Prototype Aplikasi Prediksi Kebangkrutan Dengan Model Zmijewski (Studi Kasus: Perbankan Swasta Tahun 2019-2021) - Langelo, Nathaniel Yusuf; Widayanti, Asti; Yuniar, Irna (Jurnal Sains dan Informatika, 2025)
The increasingly fierce competition in the private banking sector encourages companies to evaluate their financial health, including the risk of bankruptcy. Therefore, this research aims to develop a bankruptcy prediction application prototype using the Zmijewski model by utilizing financial data from 38 private banks listed on the Indonesia Stock Exchange (BEI). The bankruptcy prediction is conducted based on the analysis of the Zmijewski model variable data, which consists of net income, assets, and liabilities found in the company's financial statements for the years 2019-2021. The research method consists of three stages: data collection, data analysis, and application prototype development. Where the results of the analysis from the calculation of variables and the X score using the Zmijewski model show that out of the 38 banking companies studied, 21 companies are predicted to be healthy and 17 companies are predicted to go bankrupt. The development of the application prototype consists of designing a flowchart, which illustrates the application usage flow, designing an ER diagram where there are 4 main tables used, namely the bank table, variable table, component table, and model table, and then designing a use case diagram where there is 1 actor and 9 activities performed. The design results were developed into an application prototype, and the application output shows the same X Score and bankruptcy prediction as the data analysis results.